Effects of some limnological factors on the growth of Nelumbo nucifera Gaertner - Alfasane, Md Almujaddade; Khondker, Moniruzzaman; Begum, ZN Tahmida (Bangladesh Journal of Botany, 2010)
Nelumbo nucifera Gaertner was grown in a mesoscale culture by sowing seeds in cow dung compost and loamy soil (1 : 1). Rhizomes and young plantlets under ex-situ condition did not survive but germination was possible via seeds where the rate of germination was 50% and seedlings less than four months old also grew. Leaf area positively correlated with air temperature, water temperature, PAR, day length, rainfall, relative humidity, NO3-N, Chl a and phaeopigment. Petiole length showed positive correlation with rainfall, relative humidity and pH. Highest growth and flowering were found to be associated with a water depth of 100 cm under full sunshine and high nutrient conditions. Under shaded condition, plants did not produce flowers. Water flow rate of 50 ml/sec in the culture pit hampered flowering. Flowering was observed only in the stagnant condition. Key words: Nelumbo nucifera; Growth; Limnological factors DOI: 10.3329/bjb.v38i2.5137 Bangladesh J. Bot. 38(2): 133-138, 2009 (December)